Hubungan dinamis jumlah uang beredar (M2), suku bunga kebijakan BI Rate, pengeluaran pemerintah dan inflasi di Indonesia - Nur Aisyah, Indah; Hodijah , Siti; Vyn Amzar, Yohanes (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to determine and analyze the long-term and short-term dynamic relationship of the money supply (M2), the BI-Rate policy interest rate (BI-Rate), government spending, and inflation in Indonesia. For 25 years or from the period 1998 to 2023. In addition, it is also to determine the changes in each period in the variables of the money supply (M2), the BI-Rate policy interest rate (BI-Rate), government spending, and inflation in Indonesia. The data selected in this study are annual data from 1998-2023, obtained through Bank Indonesia and SEKI (Indonesian Economic and Financial Statistics). The method used in this study is the Vector Error Correction Model (VECM). The results of this study show changes in the variables of the money supply (M2), the BI-Rate policy interest rate, government spending and interest rates fluctuate throughout the study period. Based on the results of the Vector Error Correction Model (VECM) test with the granger causality test, it shows a one-way dynamic relationship between variables. The results of the IRF and FEVD tests prove that in the long term each variable significantly influences each other.